PENGARUH SEMANGAT KATEKIS BAGI PELAKSANAAN MAGANG PADA MAHASISWA STKIP WIDYA YUWANA - Satitis, Hening; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2020)
The church cannot be separated from the existence and involvement of its citizens. No strings attached, every member of the Church devotes himself to the growth and development of the Church. One of the members of the Church is a catechist. Catechists proclaim the Good News centered on Jesus Christ. The personal relationship of the catechist with Christ becomes the spirit of the catechist in carrying out his mission. The spirit should have been lived by catechists since becoming a catechist candidate during his education. The question is have the catechist candidates lived the spirit correctly? Is there a catechist spirit that is lived up by the catechist candidate has an impact on the implementation of internships at schools and parishes? To get answers to these questions research is needed. This study uses a qualitative method. The research respondents were students of STKIP Widya Yuwana in the 8th semester of the 2018/2019 academic year. Research respondents numbered 9 people. The purpose of this study is to find out whether there is an influence of the spirit of catechism in the implementation of student internships organized by STKIP Widya Yuwana or not. Based on the results of the study, as many as 55.5% of respondents stated that the basis which is lived up, then 44.4% of respondents said that the spirit of the catechist is the spirit within the catechist. Furthermore, 3 respondents 33.3% stated that the spirit of catechism is the spirit of the catechist and comes from God. Furthermore, 1 respondent stated that the spirit of the catechist originated from role models. All respondents namely 100% stated that the spirit of the catechist greatly influenced the implementation of the internship. Some influences that can be mentioned are: first, through the spirit of being responsible, humble and loyal. Second, through the spirit can act and say according to the spirit of Christ. Third, through the spirit can build awareness to serve. Fourth, through the spirit, it can be strong in dealing with problems. The fifth, effect but the results are not clear.